2019
DOI: 10.1128/mbio.01237-19
|View full text |Cite
|
Sign up to set email alerts
|

Tad Pili Play a Dynamic Role in Caulobacter crescentus Surface Colonization

Abstract: Bacterial surface attachment is mediated by filamentous appendages called pili. Here, we describe the role of Tad pili during surface colonization of Caulobacter crescentus. Using an optical trap and microfluidic controlled flow conditions to mimic natural environments, we demonstrated that Tad pili undergo repeated dynamic cycles of extension and retraction. Within seconds after establishing surface contact, pilus retraction reorients cells into an upright position, promoting walking-like movements against th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 57 publications
(129 reference statements)
1
43
0
1
Order By: Relevance
“…Therefore, c-di-GMP-mediated maintenance of proper MSHA extension/retraction dynamics is likely key for mediating long-term V. cholerae surface attachment and downstream biofilm formation. A similar mechanism has been proposed in C. crescentus, where heightened c-di-GMP promotes Tad pilus retraction that not only aids in initial surface attachment, but also promotes flagellum-surface contacts that initiate production of the holdfast to facilitate long-term attachment 23 . However, even though correlations between secondary messenger signaling and pilus extension/retraction dynamics have been observed, the relationship between these signals/events are likely to be complex with both short-and long-term multigenerational temporal correlations.…”
Section: Daughter Cellmentioning
confidence: 53%
See 3 more Smart Citations
“…Therefore, c-di-GMP-mediated maintenance of proper MSHA extension/retraction dynamics is likely key for mediating long-term V. cholerae surface attachment and downstream biofilm formation. A similar mechanism has been proposed in C. crescentus, where heightened c-di-GMP promotes Tad pilus retraction that not only aids in initial surface attachment, but also promotes flagellum-surface contacts that initiate production of the holdfast to facilitate long-term attachment 23 . However, even though correlations between secondary messenger signaling and pilus extension/retraction dynamics have been observed, the relationship between these signals/events are likely to be complex with both short-and long-term multigenerational temporal correlations.…”
Section: Daughter Cellmentioning
confidence: 53%
“…Yet in other bacteria, c-di-GMP impact on type IV pilus production is mediated by different mechanisms. In Caulobacter crescentus, low to intermediate levels of c-di-GMP promote Tad pilus production, while high concentrations promote pilus retraction 23 . In Pseudomonas aeruginosa, while the PilB extension ATPase does not directly bind c-di-GMP 48 , a secondary protein FimX binds c-di-GMP to promote PilB localization to the assembly machinery and pilus elaboration [48][49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is that, upon surface contact, force generation leads to structural rearrangements within the filament that locks pili in the retraction state, which, in turn, prevents pilus extension and reincorporation of subunits, leading to elevated PilA levels in the inner membrane and subsequent activation of c-di-GMP signaling. Recent work showed that the second-messenger c-di-GMP itself also affects pilus dynamics, promoting increased activity at intermediate levels and retraction of pili at peak concentrations (49). Thus, blocking retraction of an individual pilus likely induces a positive feedback loop to induce retraction of additional pili at the cell pole, leading to robust surface sensing.…”
Section: Discussionmentioning
confidence: 99%